2018
DOI: 10.3171/2016.9.jns161431
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of long-term outcome after brain arteriovenous malformation rupture: the RAP score

Abstract: OBJECTIVE The authors aimed to design a score for stratifying patients with brain arteriovenous malformation (BAVM) rupture, based on the likelihood of a poor long-term neurological outcome. METHODS The records of consecutive patients with BAVM hemorrhagic events who had been admitted over a period of 11 years were retrospectively reviewed. Independent predictors of a poor long-term outcome (modified Rankin Scale score ≥ 3) beyond 1 year after admission were identified. A risk stratification scale was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
(27 reference statements)
1
13
0
5
Order By: Relevance
“…5 ICH, ICH volume, intraventricular hemorrhage, and Glasgow Coma Scale have been associated with outcome in BAVM rupture. 1,6 In this retrospective cohort, S100B elevation appears to be a stronger prognostic marker than any of the imaging markers studied. S100Bmax48>0.5 µg/L demonstrated higher sensitivity and specificity than an ICH volume ≥60 mL in predicting in-hospital mortality.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…5 ICH, ICH volume, intraventricular hemorrhage, and Glasgow Coma Scale have been associated with outcome in BAVM rupture. 1,6 In this retrospective cohort, S100B elevation appears to be a stronger prognostic marker than any of the imaging markers studied. S100Bmax48>0.5 µg/L demonstrated higher sensitivity and specificity than an ICH volume ≥60 mL in predicting in-hospital mortality.…”
Section: Discussionmentioning
confidence: 66%
“…Prognostic markers provide a basis for decision-making regarding the most appropriate level of care in neurocritically ill patients. 1 Prognosis is a major thematic domain of questioning by relatives of intensive care unit patients. 4 Providing relatives with high-quality prognostic information enhances their ability to actively participate in the decision-making process regarding aggressive therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Markers of initial severity following BAVM rupture as well as long-term outcome have been widely studied [1,[7][8][9]. In contrast, studies evaluating the impact of early complications (and their incidence) such as rebleeding or ischemia remain scarce [5,6,10].…”
Section: Discussionmentioning
confidence: 99%
“…In this series, and also in the existing literature, it has been demonstrated that deep venous drainage poses a significant risk to poor outcome in surgically treated AVM patients. [21][22][23]…”
Section: Influence Of Anatomic Factors On Outcomementioning
confidence: 99%